Basic performances and potential research problems of strain hardening geopolymer composites: A critical review. (14th June 2021) - Lyu, Bang-Cheng; Ding, Cong; Guo, Li-Ping; Chen, Bo; Wang, Ai-guo
Highlights: Critical review on strain hardening geopolymer composites technology. Effect of material composition on strain hardening geopolymer composites performances. Complex material design and microstructure changes in composites. Existing problems in shrinkage, carbonation and efflorescence. Abstract: Changing the property of concrete from brittleness to ductility and toughness is one of the goals pursued by researchers in past decades. Under tensile load, the strain-softening failure model and the consequent low durability is not suitable for the concrete structures, while the emergence of strain hardening cementitious composites (SHCC) characterized with multiple cracking and strain hardening has provided a solution. Through progressive research on geopolymer composites, the feasibility of strain hardening geopolymer composites (SHGC) with green features has also been verified. However, geopolymer differ from Portland-cement system in the reaction mechanism, chemical composition, microstructure and mechanical properties, which lead to sensitive changes in the properties of matrix, fiber-matrix interfacial zone and composites. Those differences of SHGC may weaken the capacity of fiber bridging and hinder the realization of strain hardening behavior. Therefore, on the basis of latest researches of SHGC, the effects of material composition on the performances of SHGC were reviewed. Meanwhile, the potential problems were put forward and further analyzed the necessity of research from the perspectives of material design, microstructure and interface, shrinkage, carbonation and efflorescence.